Islamic Management Practices in Financial Institutions: Case Studies From Islamic Economics, Banking And Finance - Faridah Hj. Hassan (Journal of Islamic Management Studies, 2022)
Islamic Management Practices in Financial Institutions: Case Studies from Islamic Economics, Banking and Finance Authored and Publisher: Prof. Khaliq Ahmad and published by Routledge (Taylor & Francis), 605 Third Avenue, New York, NY 10158, Year 2022. Reviewed by Prof. Dr. Faridah Hj Hassan, Universiti Teknologi MARA